Act 1474 of 2011: A weapon against corruption? (2014)
This paper presents an analysis of neoliberalism in Colombia since President Cesar Gaviria in 1990 where changes were developed; as the incorporation of private companies in the provision of services that were unique to the state, as well as reforms of the Constitution which raises the issue of the General Staff in Government Procurement in Article 150, including the creation of the Act 80 of 1993 organized by the rules and principles governing contracts with state agencies and is comprised of, regulations on its scope, aims and principles of recruitment, ineligibility and incompatibility to contract, content, form and interpretation of state contract, nullity contracts, contract settlement, control of the contractual management and resolution of contractual disputes; up to the 1474 Act of 2011 known as the Statute of corruption in which the federal government intends to end the scourge of corruption, minimizing somehow evil called corruption that is immersed in the myriad contracts made by the various public authorities in Colombia.